Glycaemic index and glycaemic load values of commonly consumed foods in the United Arab Emirates. - Al Dhaheri, A; Henry, C; Mohamad, M; Ohuma, E; Ismail, L; Al Meqbaali, F; Jarrar, A (Cambridge University Press, 2017)
Glycaemic index (GI) and glycaemic load (GL) values of some commonly consumed foods in the United Arab Emirates were determined with an aim of adding these values to the existing international table of GI and GL values. In all, eighteen test foods categorised into breads (n 5), entrée dishes (n 3), main dishes (n 5) and sweet dishes (n 5) were tested. For each test food, at least fifteen healthy participants consumed 25 or 50 g available carbohydrate portions of a reference food (glucose), which was tested three times, and a test food after an overnight fast, was tested once, on separate occasions. Capillary blood samples were obtained by finger-prick and blood glucose was measured using clinical chemistry analyser. A fasting blood sample was obtained at baseline and before consumption of test foods. Additional blood samples were obtained at 15, 30, 45, 60, 90 and 120 min after the consumption of each test food. The GI value of each test food was calculated as the percentage of the incremental area under the blood glucose curve (IAUC) for the test food of each participant divided by the average IAUC for the reference food of the same participant. The GI values of tested foods ranged from low (55 or less) to high (70 or more). The GI values of various breads and rice-containing dishes were comparable with previously published values. This study provides GI and GL values of previously untested traditional Emirati foods which could provide a useful guide on dietary recommendations for the Emirati population.